The Influence Of Speed, Agility, Quickness (SAQ) Exercise On Agility And Speed - Surawan Surawan; Setyo Harmono; Budiman Agung Pratama (UNIVERSITAS NEGERI MAKASSAR, 2022)
The importance of agility and speed in football players in an effort to get maximum achievement and considering the type of Speed, Agility, Quickness (SAQ) training program, is a method that can be used to increase agility and speed, this study aims to determine the effect of speed, agility, quickness (SAQ) training on agility and speed in football extracurricular students of SMK PGRI 9 Ngawi Regency. This study uses a quantitative approach, the type of research is experimental research, the research design uses rondomized control group pretest-posttest, the sample is 30 people, while agility data is collected using the Illinois agility test instrument and the 20-meter running test. The data analysis technique used is an independent sample t-test. The results showed that the sig value of 0.001 < 0.05 which shows that there is an influence of speed, agility, quickness (saq) training on agility and speed in extracurricular football students of SMK PGRI 9 Ngawi Regency, This is seen from the average pre-test and posttest values of speed, agility, quickness (saq) training has a change of 2.71 to agility and 2.41 to speed, it can be concluded that the speed training method, Agility, Quickness (SAQ) is better for increasing agility.